Resistance to lean mass gain in constitutional thinness in free‐living conditions is not overpassed by overfeeding. Issue 5 (10th April 2020) - Ling, Yiin; Galusca, Bogdan; Martin, François‐Pierre; Bartova, Simona; Carayol, Jérôme; Moco, Sofia; Epelbaum, Jacques; Grouselle, Dominique; Boirie, Yves; Montaurier, Christophe; Cuenco, Joyceline; Minnion, James S.; et al.
Abstract: Background: Constitutional thinness (CT), a non‐malnourished underweight state with no eating disorders, is characterized by weight gain resistance to high fat diet. Data issued from muscle biopsies suggested blunted anabolic mechanisms in free‐living state. Weight and metabolic responses to protein caloric supplementation has not been yet explored in CT. Methods: A 2 week overfeeding (additional 600 kcal, 30 g protein, 72 g carbohydrate, and 21 g fat) was performed to compare two groups of CTs (12 women and 11 men) to normal‐weight controls (12 women and 10 men). Bodyweight, food intake, energy expenditure, body composition, nitrogen balance, appetite hormones profiles, and urine metabolome were monitored before and after overfeeding. Results: Before overfeeding, positive energy gap was found in both CT genders (309 ± 370 kcal in CT‐F and 332 ± 709 kcal in CT‐M) associated with higher relative protein intake per kilo (1.74 ± 0.32 g/kg/day in CT‐F vs. 1.16 ± 0.23 in C‐F, P < 0.0001; 1.56 ± 0.36 in CT‐M vs. 1.22 ± 0.32 in C‐M, P = 0.03), lower nitrogen (7.26 ± 2.36 g/day in CT‐F vs. 11.41 ± 3.64 in C‐F, P = 0.003; 9.70 ± 3.85 in CT‐M vs. 14.14 ± 4.19 in C‐M, P = 0.02), but higher essential amino acids urinary excretion (CT/C fold change of 1.13 for leucine and 1.14 for arginine) in free‐living conditions. After overfeeding, CTs presented an accentuated positive energy gap, still higher than in controls (675 ± 540 in CTs vs. 379 ± 427 in C, P = 0.04). Increase in lean mass was induced in both controls genders but not in CTs (a trend was noticed in CT women), despite a similar nitrogen balance after overfeeding (5.06 ± 4.33 g/day in CTs vs. 4.28 ± 3.15 in controls, P = 0.49). Higher anorectic gut hormones' tone, glucagon‐like peptide 1 and peptide tyrosine tyrosine, during test meal and higher snacking frequency were noticed before and after overfeeding in CTs. Conclusions: The blunted muscle energy mechanism, previously described in CTs in free‐living state, is associated with basal saturated protein turn over suggested by the concordance of positive nitrogen balance and an increased urine excretion of several essential amino acids. This saturation cannot be overpassed by increasing this spontaneous high‐protein intake suggesting a resistance to lean mass gain in CT phenotype.